Langerhans cell histiocytosis associated with recurrent pneumothorax: a case report - Ökten, Ayşenur; Mocan, Hilal; Erduran, Erol; Aslan, Yakup; Gümele, Halit R.; Özoran, Yavuz (The Turkish Journal of Pediatrics, 1996)
Pulmonary involvement of Langerhans cell histiocytosis (LCH) is an uncommon but important cause of pulmonary fibrosis and honeycombing in young adults. Rarely, pulmonary LCH may be complicated by spontaneous pneumothorax. It may be isolated or associated with multiple organ involvement. We describe here a case of LCH with diabetes insipidus, skin lesions and pulmonary involvement in a 15-year-old boy. The case was complicated by four episodes of spontaneous pneumothorax with typical radiologic findings of pulmonary LCH. His presentation, radiologic findings, treatment and clinical course during three-years of follow-up are discussed.